Safety of biologics in rheumatoid arthritis. (August 2012) - Horton, Sarah C; Nam, Jackie L; Buch, Maya H
Placebo-controlled trials of biological therapies in the treatment of rheumatoid arthritis have demonstrated significant efficacy with acceptable safety profiles. Nevertheless, while biologic treatment is well established, toxicity concerns remain an area of focus; both inter- and intra-class differences in targeted drugs are associated with different safety issues. Understanding these is important to guide therapy choice in the context of disease characteristics and comorbidity. Long-term safety data for the earliest introduced biologics (TNF-α inhibitors; infliximab, etanercept and adalimumab) are becoming available from large observational cohorts, such as national registries, and will be discussed in this review. For the more recently available treatments (certolizumab pegol, golimumab, rituximab, tocilizumab and abatacept), data from long-term extension studies of trials will be examined.